Biopsychosocial Markers of Body Image Concerns in Patients with Head and Neck Cancer: A Prospective Longitudinal Study - Justine G. Albert; Christopher Lo; Zeev Rosberger; Saul Frenkiel; Michael Hier; Anthony Zeitouni; Karen Kost; Alex Mlynarek; Martin Black; Christina MacDonald; Keith Richardson; Marco Mascarella; et al. (Current Oncology, 2022)
(1) Background: Patients and survivors of head and neck cancer (HNC) are at a high risk of developing body image concerns. Despite the prevalence of body image concerns in patients with HNC, there is a lack of longitudinal research exploring the wide array of its associated determinants. The current longitudinal study examined the determinants and longitudinal course of body image dissatisfaction in patients with HNC. (2) Methods: Patients participated in Structured Clinical Interviews and self-administered questionnaires at four time-points: (T1) upon cancer diagnosis, (T2) at 3 months post-diagnosis, (T3) at 6 months post-diagnosis, and (T4) at 12 months post-diagnosis. They also underwent a disfigurement rating on an objective scale. (3) Results: Two hundred and twenty-four patients participated in our study. Fourteen percent to twenty-eight percent of patients reported at least moderate body image concerns across time points, with the lowest rates at baseline and the highest at 3 months (T1). It was found that patients more predisposed to developing higher levels of body image concerns presented physical markers (i.e., advanced cancer stage, lower physical functioning, higher disfigurement), psychosocial markers (i.e., higher depression, higher anxiety, and higher levels of coping with denial), and health disparities (i.e., younger age, female sex, French language, and marital status, with divorced and widowers most affected). (4) Conclusions: The findings of this study highlight the multifaceted nature of body image concerns in patients with HNC and its biopsychosocial determinants. Clinicians should pay specific attention to these biopsychosocial markers in their clinics to predict high levels of body image concerns and tailor communication/refer for support accordingly.